Computational study of novel pentacene derivatives: Prediction of structural, electronic, and optical properties. (5th October 2022) - Petralia, Salvatore; Forte, Giuseppe
Abstract: Several properties of a series of novel disubstituted pentacenes, in which the substituents are donor and acceptor groups, were investigated by using the ab initio methods. In particular, the role of different substitution positions for acceptor group was explored. Calculations predict that pentacene derivatives were highly soluble and oxidatively stable than the unsubstituted pentacene. Simulated absorption spectra show that 9‐nitropentacen‐2‐amine (PD2 ) exhibits three absorption bands in the ultraviolet and visible regions. In general, substituents have important impact on the first hyperpolarizability value, and a remarkable enhancement of static second hyperpolarizability is revealed in this study; however, further investigations are required to confirm this finding. Molecular dynamics simulations of the solid state suggest that a material based on 9‐nitropentacen‐2‐amine and 10‐nitropentacen‐2‐amine could exhibit low resistivity due to the potential amount of π–π stacking. The results emphasize the potential of using the herein studied pentacene‐based compounds, with particular reference to PD2, for future applications in the optoelectronic and photonic fields. Abstract : The article examines electronic, optic and structural properties of novel disubstituted pentacene derivatives (x‐nitropentacen‐2‐amine, x = 8, 9, 10, 11) by using DFT and MD approaches. Solubility in organic solvents and photostability are discussed, and UV/VIS absorption, NLO properties, and potential disruption of the herringbone arrangement in the solid state are predicted.